2015
DOI: 10.1021/acs.organomet.5b00218
|View full text |Cite
|
Sign up to set email alerts
|

2,2,3,3-Tetrafluoronickelacyclopentanes Generated via the Oxidative Cyclization of Tetrafluoroethylene and Simple Alkenes: A Key Intermediate in Nickel-Catalyzed C–C Bond-Forming Reactions

Abstract: Oxidative cyclization of tetrafluoroethylene (TFE) and ethylene with Ni(0) resulted in the formation of a five-membered nickelacycle. In the presence of PPh 3 as an auxiliary ligand, the partially fluorinated five-membered nickelacycle was isolated and the structure was determined by X-ray analysis. This nickelacycle was found not only to react stoichiometrically with enones to give a cross-trimerization product but also to be a key reaction intermediate in the Ni(0)-catalyzed cotrimerization of TFE and ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 79 publications
0
42
0
Order By: Relevance
“…The exposure of (phen)CuPh (22), 30 which was prepared by the reaction of 5,5 dimethyl 2 phenyl 1,3,2 dioxaborinane 8a, CuO t Bu, and 1,10 phenanthroline (phen), to TFE in THF at 40 for 24 h resulted in the clean formation of (phen) CuCF 2 CF 2 Ph (23) in 88% yield as a brown solid (Scheme 14). 31 Although organoboron compounds are less common in the preparation of organocopper reagents, 32 their use confers great advantages with regard to ease of handling and functional group tolerance.…”
Section: Cu(i) Mediated Diarylation Of Tetra Uoroethylenementioning
confidence: 99%
See 4 more Smart Citations
“…The exposure of (phen)CuPh (22), 30 which was prepared by the reaction of 5,5 dimethyl 2 phenyl 1,3,2 dioxaborinane 8a, CuO t Bu, and 1,10 phenanthroline (phen), to TFE in THF at 40 for 24 h resulted in the clean formation of (phen) CuCF 2 CF 2 Ph (23) in 88% yield as a brown solid (Scheme 14). 31 Although organoboron compounds are less common in the preparation of organocopper reagents, 32 their use confers great advantages with regard to ease of handling and functional group tolerance.…”
Section: Cu(i) Mediated Diarylation Of Tetra Uoroethylenementioning
confidence: 99%
“…40 The X ray diffraction study of 28 clearly demonstrated that the nickelacyclopentane framework was derived from one TFE and one ethylene unit ( Figure 3). Further treatment of 28 with ethylene led to the formation of 5,5,6,6 tetra uoro 1 hexene (29) in 80% yield, and (η 2 CH 2 CH 2 )Ni(PPh 3 ) 2 was generated concomitantly in the crude reaction mixture.…”
Section: Ni(0) Catalyzed Linear Selective Co Trimerization Of Tfe Andmentioning
confidence: 99%
See 3 more Smart Citations